‘Buckle up and fasten that belt!’ metal belts in the Early and middle Bronze Age - Prell, Silvia (2019)
Among the many finds recovered from Tell el-Dabʿa are five decorated metal sheets, or belts, that were most probably originally sewn onto a piece of leather or textile. Such metal belts are a very special feature attested for the first time in Early Bronze Age Mesopotamia. Their occurrence in the archaeological record is limited to tombs that featured several significant finds, including weapons, in their inventory. The grave goods highlight the importance, status and wealth of the interred deceased. The design of metal belts within the distribution area in the Middle Bronze Age is very similar; the decoration, if any, is composed of differing arrangements of concentric circles of varying sizes. According to some Northern Levantine and Anatolian metal figurines, the belts were worn around the waist and buckled at the front. Metal belts were still worn in the Late Bronze and Iron Ages, as attested by statues and actual finds.1 The following article adds to a number of publications on metal belts,2 collecting all known attestations dating up to the end of the Middle Bronze Age. The aim of this paper is to determine their distribution range and elucidate their contexts to mirror networks of people sharing a similar cultural background and ancient trade connections. In addition to the elongated metal belts known from Tell el-Dabʿa, possible parts of belts, such as discs and belt fasteners, are also presented in the scope of this article.
Keywords: Tell el-Dabʿa; metal belts; Middle Bronze Age